Correlation Between brGDGTs Distribution and Elevation From the Eastern Qilian Shan - Wang, Hansheng; Gao, Peng; Yang, Rui; Nie, Junsheng; Cao, Bo; Zhou, Aifeng; Pan, Baotian; Chen, Lin; Peng, Tingjiang (Frontiers in Earth Science, 2022)
A clear understanding of the uplift history of the Tibetan Plateau is key to correctly understanding its uplift mechanisms and impacts on Asian environment. However, consensus has not been reached regarding the uplift history of the Tibetan Plateau, mainly because of lack of well-calibrated paleoaltimetry proxies and lack of knowledge of how to correctly apply them to the past. Branched glycerol dialkyl glycerol tetraethers (brGDGTs) is a promising paleoaltimetry proxy because these large molecules tend to get preserved in sediments and this proxy has a clear relationship with mean annual air temperature (MAAT), circumventing convoluted impact of precipitation or isotope variations on isotope-based paleoaltimetry proxies. As a result, many calibrations have been done linking brGDGTs with paleoelevation. Qilian Shan of the northeastern Tibetan Plateau is a key place testing previous models regarding the uplift model of the Tibetan Plateau. However, no modern calibration equation linking brGDGTs with MAAT is available. Here, we presented the first calibration equation between brGDGTs and MAAT from the eastern Qilian Shan with elevation ranging from 2055 to 3300 m (MAAT = – 15.50 + 49.55 × MBT'5ME (R2 = 0.89, P < 0.001, RMSE = 1.07 ℃)). We further established the calibration between MBT'5ME-derived MAAT and elevation. This dataset lays the foundation to understand uplift history and environmental variations of the northeastern Tibetan Plateau area.